“La actividad física y el bienestar emocional de los estudiantes’’ - Páez Zambrano, Cristian Ismael (2023)
Currently, the teaching-learning process presents many changes that demand new capabilities to respond to the needs that students require and that today's society demands, likewise these should be focused on promoting physical activity, since it is the way to improve the emotional condition and obtain a full welfare, thus improving the lifestyle of people. The methodology used was based on the interpretative approach, which allowed understanding the reality of the social context in its own nature; it also responds to a qualitative research; with a research design based on content analysis, because it allows investigating the content through the classification of categories; The method used was inductive; and the collection of information was carried out through the interview technique, with its interview guide instrument directed to the teacher and parent, and the observation technique with its observation guide instrument directed to the student, which allowed obtaining valuable information about the variables of the study. The educational proposal was the design of a guide based on varied physical activities with contents that are easy to understand and execute for the students of the Guaranda Basic Education School, which will allow the enhancement of sports practice and mental wellbeing. The result is framed in the reflection, product of the deep analysis of the collected data. This project contributes to develop new physical practices that help to maintain a balanced wellbeing, making the practices more pleasant and interesting, taking into account that physical activity has a great incidence and importance in the emotional wellbeing of the child, since it grants satisfactions according to the existential needs of being, having, doing and being.